THE ADDED VALUE OF PURPLE SWEET POTATO INTO PROCESSED PURPLE SWEET MILK PIE IN HARAU DISTRICT, LIMAPULUH KOTA REGENCY: NILAI TAMBAH UBI JALAR UNGU MENJADI OLAHAN PIE SUSU UBI UNGU DI KECAMATAN HARAU, KABUPATEN LIMAPULUH KOTA - Putri, Amelia; Walfindo, Ikhsan (JURNAL AGRIBISAINS, 2022)
Purple sweet potato is an agricultural commodity whose productivity is quite large, but currently the processing of purple sweet potato products is still not widely circulated. The calculation of added value and business feasibility based on purple sweet potato has never been done. This research was carried out with the aim of calculating whether processing purple sweet potato into purple sweet potato milk pie is feasible to be carried out on an ongoing basis. The results of the study explained that the added value and the ratio of added value obtained from changing purple sweet potato into purple sweet potato milk pie was Rp. 131.790.- with a value added ratio of 58,57%.